2007
DOI: 10.1523/jneurosci.3739-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization and Neurotransmitter Regulation of Vasopressin Gene Expression in the Rat Suprachiasmatic NucleusIn Vitro

Abstract: Vasopressin (VP) transcription in the rat suprachiasmatic nucleus (SCN) in organotypic culture was studied by in situ hybridization histochemistry using an intron-specific VP heteronuclear RNA probe. The circadian peak of VP gene transcription in the SCN in vitro is completely blocked by a 2 h exposure to tetrodotoxin (TTX) in the culture medium, and this TTX inhibition of VP gene transcription is reversed by exposure of the SCN to either forskolin or potassium depolarization. This suggests that an intrinsic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…We found that TTX treatment results in reduced synchrony among SCN cells and that its removal allows the circadian oscillators to resynchronize, consistent with prior reports based on Per1 or Per2 gene activity and intracellular calcium levels (Yamaguchi et al 2003; Maywood et al, 2006; Aton et al, 2006; Webb et al, 2009; Ko et al, 2010; Enoki et al, 2012; Evans et al, 2013; Baba et al, 2008; Rusnak et al, 2007). During resynchronization, the period of the cells in the dorsal SCN gradually approached the period of the ventral SCN until they reached a steady state phase relationship with the ventral peaking after the dorsal SCN each day.…”
Section: Discussionsupporting
confidence: 91%
“…We found that TTX treatment results in reduced synchrony among SCN cells and that its removal allows the circadian oscillators to resynchronize, consistent with prior reports based on Per1 or Per2 gene activity and intracellular calcium levels (Yamaguchi et al 2003; Maywood et al, 2006; Aton et al, 2006; Webb et al, 2009; Ko et al, 2010; Enoki et al, 2012; Evans et al, 2013; Baba et al, 2008; Rusnak et al, 2007). During resynchronization, the period of the cells in the dorsal SCN gradually approached the period of the ventral SCN until they reached a steady state phase relationship with the ventral peaking after the dorsal SCN each day.…”
Section: Discussionsupporting
confidence: 91%
“…MCNs are found in the SON, PVN, and a dispersed population of MCNs called the ACC nucleus. The Avp immunopositive SCN neurons, which contain only small Avp-expressing neurons, are also found in these organotypic cultures (Rusnak et al, 2007; Wray et al, 1993). We find that most of the Oxt and Avp MCNs are typically located in one slice (as shown in Fig 1), but smaller numbers of these cells from each nucleus can be found in the three other slices from a single animal.…”
Section: Resultsmentioning
confidence: 66%
“…Certain neuronal systems in the hypothalamus such as LHRH neurons in the OVLT-MPOA region (Wray et al, 1988)and the suprachiasmatic nuclei (SCN) (Belenky et al, 1996)survive exceptionally well in organotypic cultures. As a result, the SCN in organotypic culture has been an outstanding and reliable model for the study of the generation of circadian rhythms in this nucleus (Maywood et al, 2007; Maywood et al, 2006; O’Neill et al, 2008; Rusnak et al, 2007; Tominaga et al, 1994). For other neuronal phenotypes, however, such as the magnocellular neurons (MCNs) in the hypothalamo-neurohypophysial system (HNS) it has been found that while the topography of the MCNs is maintained in organotypic culture, the survival of these neurons particularly the Avp-MCNs, the PVN and SON is very poor and highly variable (House et al, 1998; Wray et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…, 1998) that rhythmic release and gene expression of AVP in the SCN depend mainly on the mechanisms endogenous to the SCN. VIP was found to be the most effective ligand in evoking a cAMP‐mitogen‐activated protein kinase signal transduction cascade leading to an increase in vasopressin gene transcription in the SCN (Rusnak et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%